Why people are key to cyber-security. Issue 6 (June 2016) - Hall, Mark
Abstract : Cyber-security is one of the great issues of our time. As organisations have become increasingly dependent on computer and data communication technology, the opportunity for thieves has grown. Couple that with the lack of national boundaries in cyberspace and the relatively low probability of being caught and the risk/reward ratio makes cybercrime much more attractive than taking a sawn-off shotgun into a bank. Experienced thieves with a plan of action in place will always locate and maliciously target the greatest source of weakness – people. But by properly engaging the people in your organisation in the battle against attackers, you can turn your biggest weakness into your greatest asset, argues Mark Hall of Redcentric.